A Liquid Chromatography of Urine 8nd lts Clinical Application - YAMAGATA, YOH; MIYAGI, HIROYUKI; TAKATA, YOSHINORI; MIURA, JUNKICHI (Japanese Journal of Clinical Chemistry, 1983)
A clinical liquid chromatograph, which consists of a completely automated liquid chromatograph combined with a microcomputer for diagnosis, and it's application to rerlal function analyses are described.The analytical rate for urinary ultraviolet-absorbing constituents using anion-exchange chromatography was twelve samples per day.The reproducibilities of retention time, peak area and absorbance ratio (A23nm/A250nm) were less than 1%, 5%, and 6%, respectively for continuous five days running. Approximately 90 morning fasting urhes were obtained from adult“healthy”subjects, inpatients and outpatients.The urine samples were stored at-20°C until used, and defrosted at room temperature in a water bath at 37°C. They were centrifuged and then the supernatant was filtered through a 0.1μm pore size membrane filter for the chromatography. Each chromatographic peak was numbered in accordance with peak identification parameters such as retention time and absorbance ratio.These peaks were rearranged in the order of peak number instead of retention time. The reconstructed chromatograms were used to discuss kidney functions in three ways. Those are (1) comparison of chromatograqhic profiles between normal and abnormal subjects,(2) correlation between creatinine clearance and a chromatographic peak,(3) correlation analysis of peak area between two specific peaks. These methods as mentioned above seem to be usefull for the estimation of pathological phases and metabolic change induced by drugs and diseases.